Describing biodiversity in the genomics era: A new species of Nearctic Cynipidae gall wasp and its genome. (10th January 2022) - Brandão‐Dias, Pedro F. P.; Zhang, Yuanmeng Miles; Pirro, Stacy; Vinson, Camila C.; Weinersmith, Kelly L.; Ward, Anna K. G.; Forbes, Andrew A.; Egan, Scott P.
ABSTRACT: Gall wasps (Hymenoptera: Cynipidae) specializing on live oaks in the genus Quercus (subsection Virentes ) are a relatively diverse and well‐studied community with 14 species described to date, albeit with incomplete information on their biology, life history and genetic structure. Incorporating an integrative taxonomic approach, we combine morphology, phenology, behaviour, genetics and genomics to describe a new species, Neuroterus valhalla sp. nov . The alternating generations of this species induce galls on the catkins and stem nodes of Quercus virginiana and Quercus geminata in the southern United States. We describe both generations in the species' life cycle, and primarily use samples from a population in the centre of Houston, Texas, thus serving as an example of the undescribed biodiversity still present in well‐travelled urban centres. In parallel, we present a draft assembly of the N. valhalla genome providing a direct link between the type specimen and reference genome. The genome of N. valhalla is the smallest reported to date within the tribe Cynipini, providing an important comparative contrast to the otherwise large genome size of cynipids. While relatively small, the genome was found to be composed of >64% repetitive elements, including 43% unclassified repeats and 11% retrotransposons. A preliminary ab initio and homology‐based annotation revealed 32, 005 genes, and a subsequent orthogroup analysis grouped 18, 044 of these to 8186 orthogroups, with some evidence for high levels of gene duplications within Cynipidae. A mitochondrial barcode phylogeny linked each generation of the new species and a phylogenomic ultraconserved element (UCEs) phylogeny indicates that the new species groups with other Nearctic Neuroterus . However, both phylogenies present the genus Neuroterus in North America as polyphyletic. Abstract : Incorporating an integrative taxonomic approach, we describe a new species, Neuroterus valhalla sp. nov. alongside its genome sequence, highlighting the parallel between a type specimen and a reference genome. We describe it primarily from a population in the centre of Houston, Texas, thus serving as an example of the undescribed biodiversity still present in well‐travelled urban centres. The genome of N. valhalla is the smallest reported to date within the tribe Cynipini, with evidence of extensive gene duplications, sparking a discussion on the mechanisms behind Cynipidae's large genomes.